Expansão da escola básica e a relação capital, trabalho e educação no Brasil dos anos 1970 - FERREIRA, João Roberto Resende (2012)
FERREIRA, João Roberto Resende. Expansion of basic education and the relationship capital, labor and education on the 70 s in Brazil. 2011. 125 pages. Thesis (Graduate Education Program) Faculdade de Educação, Universidade Federal de Goiás, Goiânia, 2011. This study is a bibliographical research which belongs to the research field of Education, Labor and Social Movements. It sets out to understand the expansion of basic education in Brazil in the context of its close relationship with capital, labor and education. The study tries to understand the logic underlying the action of capital, workers and State in relation to the school and the principles and values which inspired educational reform in the late twentieth century. It is based on the Gramscian theoretical framework in what refers to Americanism and Fordism, according to which all historical particularities require people to acquire specific formation and it is up to the different schools and intellectuals to exercise this formative function in a society of classes. In Brazil, the process of industrial expansion and unplanned urbanization generated urban contradictions and put access to education at center stage in popular struggles.